Over a million students use our free study notes to help them with their homework
If we right down all we have here we get:P(A) = X P(B) = 0.2 P(AIB) = 0.75 (P(A) knowing B). And we are looking for P(ANB). We have to use the formula of P(AIB) = P(ANB)/P(B). If we rearrange the equ...
First of all you need to understand that not every problem can be solved by sistematically applying the same set of steps or rules: sometimes you need to come up with different ways. In order to do that, ...
We are trying to get to the form of x2 + 5x + 6 = ( x + a)(x + b)6 must also factorise as 6x1 or 3x2 Let's focus first on the x terms : 5x is the sum of ax + dbx and the coefficient of these tw...
15x + 25y = 5015x + 12y = 24y = 2x = 0
Use the FOIL method, first, outside, inside, last. 1) F: The first term in the first bracket multiplies the first term in the second bracket. 2) O: The first term in the first bracket jumps outside to mul...
←
607
608
609
610
611
→
Internet Safety
Payment Security
Cyber
Essentials